1998
DOI: 10.1007/s002340050632
|View full text |Cite
|
Sign up to set email alerts
|

MRI assessment of cerebral blood volume in patients with brain infarcts

Abstract: MRI perfusion studies have focussed mainly on acute ischaemia and characterisation in ischaemia. Our purpose was to analyse regional brain haemodynamic information in acute, subacute, and chronic ischaemia. We performed 16 examinations of 11 patients on a 1.5 T MR images. Conventional and dynamic contrast-enhanced imaging were employed in all examinations. For the dynamic susceptibility sequences, a bolus (0.2 mmol/kg) of gadopentetate dimeglumine was injected. Reconstructed regional relative cerebral blood vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…All studies used the gadolinium bolus tracking method of measuring blood transit time. A variety of perfusion abnormalities were demonstrated; 1 study 56 (nϭ11) noted a heterogeneous distribution of rCBF in the expected regions of interest in all examinations; 3 6,7,55 (nϭ16 to nϭ34) documented hyperperfusion as well as delayed or absent perfusion in the region of interest; and 1 54 (nϭ11) documented no perfusion deficits in 4 of the 11 subjects despite marked clinical signs and repeat MR within 48 hours confirming infarction.…”
Section: Studies Of Pi Alonementioning
confidence: 99%
“…All studies used the gadolinium bolus tracking method of measuring blood transit time. A variety of perfusion abnormalities were demonstrated; 1 study 56 (nϭ11) noted a heterogeneous distribution of rCBF in the expected regions of interest in all examinations; 3 6,7,55 (nϭ16 to nϭ34) documented hyperperfusion as well as delayed or absent perfusion in the region of interest; and 1 54 (nϭ11) documented no perfusion deficits in 4 of the 11 subjects despite marked clinical signs and repeat MR within 48 hours confirming infarction.…”
Section: Studies Of Pi Alonementioning
confidence: 99%
“…Cerebral blood volume (CBV) is a very important measurement for the study of a number of neurological disorders that involve vascular dysregulation. These include hypertension, stroke , small brain infarcts , Alzheimer disease , astrocytoma and other brain tumors , and cerebral stenoses . The ability to separate the arterial compartment from the venous compartment of CBV may provide additional information not obtainable by imaging the total CBV [e.g., in steno‐occlusive disease of the internal carotid artery ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative measurement of cerebral blood volume (CBV, defined as ml blood in 100 ml brain) is useful for advancing our understanding of brain physiology and pathophysiology (1, 2). It has been reported that many brain disorders, including stroke (1, 3, 4) and Alzheimer's disease (5–8), are associated with abnormal CBV. Compared to cerebral blood flow (CBF), CBV has been less extensively studied, but it was recently shown to be particularly sensitive to brain tumor grade (9), and it may be a useful marker for angiogenesis and synaptogenesis (10, 11).…”
mentioning
confidence: 99%